The Usage of Paylater Among College Students: The Role of Self-Control, Hedonistic Conformity, and Family Financial Education - Nugrahanti, Yeterina Widi; Rita, Maria Rio; Restuti, Mitha Dwi; Hadiluwarso, Melina Alicia (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: The increasing phenomenon of the unwise use of Paylater in society, even among college students, is interesting to review further. This study aims to test the role of self-control and hedonistic conformity with the moderation of family financial education on the use of Paylater by university students.Design/Methodology/Approach: Primary data was obtained through a survey involving 117 respondents who have or are currently using the Paylater service. Furthermore, the data was processed using the Partial Least Squares (PLS) method.Research findings: This study produced the following findings: hedonistic conformity was proven to have a positive effect on the use of Paylater in the full sample and in two sub-samples. This finding is in line with the TPB modification used in this research, hedonic conformity as a proxy for subjective norms has been shown to contribute positively to the use of Paylater among colleege students. Meanwhile, the role of family financial education has not been proven to moderate the regression path of self-control and hedonic conformity on the use of Paylater.Theoretical Contribution/Originality: This study contributes to enriching the literature on personal financial management, especially regarding the use of Paylater based on internal and external factors of students.Practitioners/Policy Implications: These results offer recommendations for personal financial management, especially for university students, to avoid the risk of being trapped by Paylater by paying attention to their social community and prioritizing family financial education.Research Limitations/Implications: Respondents were mostly undergraduate students, so this study cannot explain the dynamics of financial behavior among undergraduate and postgraduate students who have different demographic characteristics. Therefore, future research needs to analyze different sample groups to enrich the scientific perspective. Furthermore, to provide depth of analysis, this study proposes to add other internal aspects of the individual to the TPB theoretical framework (e.g.: perception of usury and financial risk tolerance). Last but not least, regarding the development of indicators from the family financial education variable that does not yet include personal debt management education items, hence this indicator can be added as a proxy for this variable to obtain in-depth measurements.